Quantum dot light conversion film, preparation method and application thereof, and yellow light lamp for anti-ultraviolet blue-light-free chip manufacturing process

Through the preparation and application of quantum dot light conversion film, the problem that the existing technology cannot meet the light cut-off requirements of chip processes below 5nm for chips below 535nm is solved, and efficient light conversion and light output are achieved. It is suitable for ultraviolet-proof blue-ray-free chip processes Use yellow light.

CN119410276APending Publication Date: 2025-02-11TAIJIA CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411295497.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The prior art cannot meet the complete cutoff requirements for light below 535nm by chip manufacturing process below 5nm, and traditional fluorescent lamps and LED lamps cannot effectively filter light at these wavelengths.

Method used

A quantum dot light conversion film is used to mix the quantum dot concentrate with acrylic monomer and nanoparticles to form a photoconverted liquid glue, and a quantum dot light conversion film is obtained by coating and curing. The film surface forms a tightly arranged high-refractive index microlens structure to increase the light output and cut off light rays below 535 nm.

Benefits of technology

An effective cutoff of light below 535nm is achieved, and a yellow light source suitable for chip manufacturing process below 5nm is provided, which improves the luminous flux and reduces the heat generation, while avoiding the crystallization and curing of photosensitive materials such as photoresist.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410276A_ABST
    Figure CN119410276A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of optical materials, and provides a quantum dot light conversion film, a preparation method and application thereof, and a yellow lamp for an anti-ultraviolet blue-light-free chip manufacturing process. The method comprises the following steps: (1) mixing a quantum dot concentrated solution and an acrylic monomer, adding a high polymer, and carrying out secondary mixing to obtain a polymer; (2) mixing a polymer and nano-particles, adding an auxiliary agent, and dispersing to obtain light conversion liquid glue; and (3) coating and curing the light conversion liquid glue to obtain the quantum dot light conversion film. The light conversion film has the characteristics of high light conversion efficiency, adjustable emission peak position, narrow half-peak width and the like. High-refractive-index micro-lens structures which are tightly arranged are formed on the surface of the light conversion film. When the light reaches the micro-lens array, as the light-emitting surface is of a lens structure and the refractive index is improved, the light is emitted in the forward direction as much as possible, and therefore the light-emitting rate is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical materials, and in particular to a quantum dot light conversion film, a preparation method and application thereof, and a yellow light lamp for ultraviolet-proof blue-light-free chip manufacturing process. Background Art

[0002] In view of the performance of photoresist in the yellow light process and the yield of the photolithography process, and considering the visual function of the human eye to light waves, the chip process yellow light room should use special lighting. The traditional solution uses fluorescent tubes plus filters to filter light with a wavelength below 500nm. The popular LED tube plus filter solution in recent years filters light with a wavelength below 520nm. With the update and iteration of chips, process chips below 5nm have shown low power consumption and super computing power, but the 5nm process has higher requirements for lighting. Light with a wavelength below 535nm needs to be completely cut off. The above-mentioned traditional fluorescent tubes and LED tubes cannot meet the process below 5nm.

[0003] As chip manufacturing processes continue to advance, yellow light lighting has hardly changed. Traditional white fluorescent tubes are superimposed with yellow fluorescent coatings to obtain light with a cutoff wavelength of more than 500nm. The efficiency of LED light-emitting chips is much higher than that of fluorescent lamps, and they are widely used in the field of lighting. It uses high-efficiency blue light LEDs to excite phosphors of different ratios, and then superimposes a filter solution to obtain light with a cutoff wavelength of more than 520nm, and has higher luminous flux and lower heat generation. Since the conversion efficiency of phosphors is not high, the spectrum contains a large amount of blue light components, and the light energy will be greatly lost after being filtered by the filter. Therefore, providing a light source suitable for the yellow light process has become an urgent problem to be solved. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects in the prior art and provide a quantum dot light conversion film and a preparation method and application thereof, as well as a yellow light lamp for anti-ultraviolet and blue-light-free chip processing.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a quantum dot light conversion film, comprising the following steps:

[0007] (1) mixing a quantum dot concentrate and an acrylic acid monomer, and then adding a polymer to the mixture for secondary mixing to obtain a polymer;

[0008] (2) mixing the polymer and the nanoparticles and adding an auxiliary agent to disperse them to obtain a photoconvertible liquid glue;

[0009] (3) The light-conversion liquid glue is coated and cured to obtain the quantum dot light-conversion film.

[0010] Preferably, the wavelength of the quantum dot concentrate in step (1) is 580-600 nm;

[0011] The mass ratio of the quantum dot concentrate to the acrylic acid monomer is 1-20:5-50;

[0012] The polymer in step (1) is acrylic acid and / or mercaptan;

[0013] The mass ratio of the quantum dot concentrate to the polymer in step (1) is 1-20:5-50.

[0014] Preferably, the nanoparticles in step (2) are TiO2 or ZrO2; the particle size of the nanoparticles is 50 to 500 nm;

[0015] The mass ratio of the quantum dot concentrate in step (1) to the nanoparticles in step (2) is 1-20:0.5-5;

[0016] The auxiliary agent in step (2) comprises an inhibitor and a photoinitiator;

[0017] The mass of the polymerization inhibitor is 0.01 to 0.2% of the mass of the photoconverted liquid glue in step (2);

[0018] The mass of the photoinitiator is 0.5-2% of the mass of the photoconverted liquid glue in step (2).

[0019] Preferably, the coated substrate in step (3) is aluminum oxide or silicon oxide; the thickness of the substrate is 12 to 120 μm;

[0020] The thickness of the glue applied in step (3) is 50 to 200 μm;

[0021] The curing irradiation energy in step (3) is 500-3000 Mj / cm 2 .

[0022] The present invention also provides a quantum dot light conversion film prepared by the method for preparing the quantum dot light conversion film.

[0023] The present invention also provides the use of the quantum dot light conversion film in a yellow light lamp for anti-ultraviolet and blue-light-free chip manufacturing process.

[0024] The present invention also provides a yellow light lamp for ultraviolet-proof and blue-light-free chip processing. The structure of the yellow light lamp for ultraviolet-proof and blue-light-free chip processing is from top to bottom: the quantum dot light conversion film, thermal insulation film, OCA glue layer, transparent silicone layer, and miniLED blue light chip light source.

[0025] Preferably, the transparent silica gel layer contains nanoparticles; the nanoparticles are TiO2 or ZrO2;

[0026] The mass of the nanoparticles is 0.5-5% of the mass of the transparent silica gel layer.

[0027] Preferably, the OCA adhesive layer contains nanoparticles; the nanoparticles are TiO2 or ZrO2;

[0028] The mass of the nanoparticles is 1-40% of the mass of the OCA adhesive layer.

[0029] The present invention provides a method for preparing a quantum dot light conversion film, comprising the following steps: (1) mixing a quantum dot concentrate and an acrylic monomer, adding a polymer for secondary mixing to obtain a polymer; (2) mixing a polymer and nanoparticles, adding an auxiliary agent for dispersion to obtain a light conversion liquid glue; (3) coating and curing the light conversion liquid glue to obtain the quantum dot light conversion film. In the present invention, the light conversion liquid glue is coated on a water-blocking and oxygen-blocking film, and then covered with a layer of a water-blocking and oxygen-blocking film, and then cured by UV to form a light conversion film with a sandwich structure. The light conversion film not only has the characteristics of high light conversion efficiency, adjustable emission peak position, narrow half-peak width, etc., but also can be printed with various inks on the film surface, and a special optical structure is designed on the film surface to meet the requirements of light scattering, etc., and has excellent heat resistance and weather resistance. The surface of the light conversion film in the present invention forms a tightly arranged high-refractive index microlens structure. When light reaches the microlens array, since the light-emitting surface is a lens structure and the refractive index is increased, as much light as possible is emitted in the forward direction, thereby effectively improving the light output rate.

[0030] The present invention also provides a yellow light lamp for anti-ultraviolet and blue-light-free chip processing, and the structure of the yellow light lamp for anti-ultraviolet and blue-light-free chip processing is, from top to bottom, the quantum dot light conversion film, thermal insulation film, OCA adhesive layer, transparent silicone layer, and miniLED blue light chip light source. In the present invention, the yellow light lamp uses a mini LED blue light chip to excite the quantum dot material and convert the blue light into yellow light of a specific wavelength. It has the characteristics of high luminous efficiency, no blue-green light below 535nm, and will not cause crystallization and solidification of photosensitive materials such as photoresist. The mini LED chip is much higher than ordinary LED chips in luminous efficiency and uniformity, and because of the characteristics of mini LED such as small driving current, low heat generation, and long life, the lamp made of it to excite quantum dot film of a specific wavelength has incomparable advantages. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic top view of the substrate structure in Example 1;

[0032] Figure 2 This is a schematic diagram of the structure of a yellow light lamp used in the process of manufacturing ultraviolet-proof and blue-light-free chips in Example 1;

[0033] Figure 3 This is the spectrum of the yellow light lamp used in the process of anti-ultraviolet and blue-light-free chip manufacturing in Example 1;

[0034] Figure 4 This is the chromaticity diagram of the yellow light lamp used in the UV-proof blue-light-free chip process in Example 1. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a quantum dot light conversion film, comprising the following steps:

[0036] (1) mixing a quantum dot concentrate and an acrylic acid monomer, and then adding a polymer to the mixture for secondary mixing to obtain a polymer;

[0037] (2) mixing the polymer and the nanoparticles and adding an auxiliary agent to disperse them to obtain a photoconvertible liquid glue;

[0038] (3) The light-conversion liquid glue is coated and cured to obtain the quantum dot light-conversion film.

[0039] In the present invention, the wavelength of the quantum dot concentrate in step (1) is preferably 580-600 nm, more preferably 585-595 nm, and even more preferably 588-590 nm.

[0040] In the present invention, the quantum dot concentrate can be obtained commercially.

[0041] In the present invention, the mass ratio of the quantum dot concentrate to the acrylic acid monomer is preferably 1-20:5-50, more preferably 5-15:10-40, and even more preferably 8-12:20-30.

[0042] In the present invention, the polymer in step (1) is acrylic acid and / or thiol.

[0043] In the present invention, the mass ratio of the quantum dot concentrate to the polymer in step (1) is preferably 1-20:5-50, more preferably 5-15:10-40, and even more preferably 8-12:20-30.

[0044] In the present invention, the mixing speed in step (1) is preferably 200 to 1000 rpm, more preferably 300 to 800 rpm, and more preferably 400 to 600 rpm; the mixing time is preferably 20 to 60 min, more preferably 30 to 50 min, and more preferably 35 to 45 min.

[0045] In the present invention, the rotation speed of the secondary mixing in step (1) is preferably 200-1000 rpm, more preferably 300-800 rpm, more preferably 400-600 rpm; the time of the secondary mixing is preferably 20-60 min, more preferably 30-50 min, more preferably 35-45 min.

[0046] In the present invention, the nanoparticles in step (2) are TiO2 or ZrO2; the particle size of the nanoparticles is preferably 50 to 500 nm, more preferably 100 to 400 nm, and more preferably 200 to 300 nm.

[0047] In the present invention, the mass ratio of the quantum dot concentrate in step (1) to the nanoparticles in step (2) is preferably 1-20:0.5-5, more preferably 5-15:1-4, and even more preferably 8-12:2-3.

[0048] In the present invention, the mixing speed in step (2) is preferably 200 to 1000 rpm, more preferably 300 to 800 rpm, and more preferably 400 to 600 rpm; the mixing time is preferably 20 to 60 min, more preferably 30 to 50 min, and more preferably 35 to 45 min.

[0049] In the present invention, the auxiliary agent in step (2) comprises an inhibitor and a photoinitiator.

[0050] In the present invention, the polymerization inhibitor and the photoinitiator are commercially available products.

[0051] In the present invention, the mass of the polymerization inhibitor is 0.01 to 0.2% of the mass of the photoconverted liquid glue in step (2).

[0052] In the present invention, the mass of the photoinitiator is 0.5-2% of the mass of the photoconverted liquid glue in step (2).

[0053] In the present invention, the dispersion speed in step (2) is preferably 200-1000 rpm, more preferably 300-800 rpm, more preferably 400-600 rpm; the dispersion time is preferably 20-60 min, more preferably 30-50 min, more preferably 35-45 min.

[0054] In the present invention, the coated substrate in step (3) is aluminum oxide or silicon oxide; the thickness of the substrate is preferably 12 to 120 μm, more preferably 20 to 100 μm, and even more preferably 40 to 60 μm.

[0055] In the present invention, the substrate has the function of blocking water and oxygen, and the substrate is aluminum oxide or silicon oxide deposited by using a PECVD method or a magnetron sputtering method.

[0056] In the present invention, the thickness of the glue applied in step (3) is preferably 50 to 200 μm, more preferably 80 to 150 μm, and more preferably 100 to 120 μm.

[0057] In the present invention, the photoconvertible liquid glue is coated on the surface of the substrate by using a multi-roll coating, a slit coating, a drip coating or the like process, and then a layer of the substrate is covered on the surface of the glue to form a sandwich structure.

[0058] In the present invention, the curing irradiation energy in step (3) is preferably 500 to 3000 Mj / cm 2 , more preferably 1000 to 2000 Mj / cm 2 , more preferably 1500 to 1800 Mj / cm 2 ; Use ultraviolet irradiation.

[0059] The present invention also provides a quantum dot light conversion film prepared by the method for preparing the quantum dot light conversion film.

[0060] The present invention also provides the use of the quantum dot light conversion film in a yellow light lamp for anti-ultraviolet and blue-light-free chip manufacturing process.

[0061] The present invention also provides a yellow light lamp for ultraviolet-proof and blue-light-free chip processing. The structure of the yellow light lamp for ultraviolet-proof and blue-light-free chip processing is from top to bottom: the quantum dot light conversion film, thermal insulation film, OCA glue layer, transparent silicone layer, and miniLED blue light chip light source.

[0062] In the present invention, the material of the thermal insulation film is acrylic or PC.

[0063] In the present invention, the light source of the miniLED blue light chip is implanted in the substrate, a milky white light-shielding ink layer is vertically arranged around the chip light-emitting area, and then silicone is injected into it to form a silicone layer.

[0064] In the present invention, the transparent silica gel layer contains nanoparticles; the nanoparticles are TiO2 or ZrO2.

[0065] In the present invention, the mass of the nanoparticles is preferably 0.5-5% of the mass of the transparent silica gel layer, more preferably 1-4%, and even more preferably 2-3%.

[0066] In the present invention, the silica gel layer doped with nanoparticles has excellent stability and heat resistance.

[0067] In the present invention, the OCA adhesive layer contains nanoparticles; the nanoparticles are TiO2 or ZrO2.

[0068] In the present invention, the mass of the nanoparticles is preferably 1 to 40% of the mass of the OCA adhesive layer, more preferably 5 to 35%, and even more preferably 10 to 20%.

[0069] In the present invention, the OCA adhesive layer plays a bonding role and has temperature resistance, softness and high light transmittance.

[0070] In the present invention, a quantum dot light conversion film is attached to the thermal insulation film to obtain yellow light with a main emission peak in the 580-600nm band. The yellow light is filtered out by an external filter to remove the weak blue light part that is not converted into yellow light, thereby obtaining a yellow light that does not contain any band below 535nm.

[0071] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0072] Example 1

[0073] Take a quantum dot concentrate with a wavelength of 590nm, control the mass ratio of the quantum dot concentrate and acrylic acid monomer to be 10:30, mix the two and stir at 500rpm for 40min, then add acrylic acid (the mass ratio of the quantum dot concentrate and acrylic acid is 10:25), continue stirring at 500rpm for 40min to obtain a polymer; then add TiO2 (particle size is 100nm), control the mass ratio of the quantum dot concentrate and nanoparticles to be 10:1, stir at 500rpm for 40min; then add commercially available The polymerization inhibitor and the photoinitiator, the mass of the polymerization inhibitor is 0.1% of the mass of the photoconvertible liquid glue, the mass of the photoinitiator is 1% of the mass of the photoconvertible liquid glue, and the photoconvertible liquid glue is obtained by stirring at a speed of 500 rpm for 40 minutes; the photoconvertible liquid glue is coated on the surface of the water-blocking and oxygen-blocking aluminum oxide substrate (thickness is 80 μm) in a slit coating manner, and the coating thickness is 100 μm, and then the same water-blocking and oxygen-blocking aluminum oxide substrate is continued to be covered on the glue surface to form a sandwich structure, and ultraviolet irradiation is used to control the irradiation energy to 1500 Mj / cm 2 , and solidified to obtain a quantum dot light conversion film.

[0074] A miniLED blue light chip is implanted on the surface of the aluminum substrate, and a milky white light-shielding ink layer is vertically arranged around the substrate. Silicone is injected into the enclosure formed by the ink layer to form a silicone layer. The silicone layer contains TiO2, and the mass of TiO2 is 1% of the mass of the silicone layer. The substrate, milky white light-shielding ink layer and silicone layer are the base structure. The top view of the base structure is shown in the figure below. Figure 1 shown.

[0075] OCA glue is coated on the surface of the silicone layer (the OCA glue layer contains TiO2, and the mass of TiO2 is 10% of the mass of the OCA glue layer), a heat insulation film is set on the surface of the OCA glue layer (the heat insulation film is made of acrylic or PC), and a quantum dot light conversion film is covered on the surface of the heat insulation film to obtain a yellow light lamp for anti-ultraviolet and blue-light-free chip manufacturing process. Its structural schematic diagram is shown in Figure 2 shown.

[0076] The yellow light lamp prepared in this embodiment was tested for performance, and its spectrum is as follows: Figure 3 As shown, the ordinate is the relative spectral intensity and the abscissa is the spectral wavelength. Figure 3 It can be seen that the cut-off wavelength of the yellow light prepared in Example 1 is greater than or equal to 535 nm.

[0077] The yellow light lamp prepared in this example was tested for performance, and its chromaticity diagram is shown in Figure 4 As shown, from Figure 4 It can be seen that the white point coordinates of the yellow light lamp in Example 1 are x=0.5483, y=0.4416.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a quantum dot light conversion film, characterized in that: It includes the following steps: (1) mixing a quantum dot concentrate and an acrylic acid monomer, and then adding a polymer to the mixture for secondary mixing to obtain a polymer; (2) mixing the polymer and the nanoparticles and adding an auxiliary agent to disperse them to obtain a photoconvertible liquid glue; (3) The light-conversion liquid glue is coated and cured to obtain the quantum dot light-conversion film.

2. The method for preparing a quantum dot light conversion film according to claim 1, characterized in that: The wavelength of the quantum dot concentrate in step (1) is 580-600 nm; The mass ratio of the quantum dot concentrate to the acrylic acid monomer is 1-20:5-50; The polymer in step (1) is acrylic acid and / or mercaptan; The mass ratio of the quantum dot concentrate to the polymer in step (1) is 1-20:5-50.

3. The method for preparing a quantum dot light conversion film according to claim 1 or 2, characterized in that: The nanoparticles in step (2) are TiO2 or ZrO2; the particle size of the nanoparticles is 50 to 500 nm; The mass ratio of the quantum dot concentrate in step (1) to the nanoparticles in step (2) is 1-20:0.5-5; The auxiliary agent in step (2) comprises an inhibitor and a photoinitiator; The mass of the polymerization inhibitor is 0.01-0.2% of the mass of the photoconverted liquid glue in step (2); The mass of the photoinitiator is 0.5-2% of the mass of the photoconverted liquid glue in step (2).

4. The method for preparing a quantum dot light conversion film according to claim 3, characterized in that: The coated substrate in step (3) is aluminum oxide or silicon oxide; the thickness of the substrate is 12 to 120 μm; The thickness of the glue applied in step (3) is 50 to 200 μm; The curing irradiation energy in step (3) is 500-3000 Mj / cm 2 .

5. The quantum dot light conversion film prepared by the method for preparing a quantum dot light conversion film according to any one of claims 1 to 4.

6. Application of the quantum dot light conversion film described in claim 5 in yellow light lamps for anti-ultraviolet and blue-light-free chip manufacturing processes.

7. A yellow light lamp for UV-proof and blue-light-free chip manufacturing process, characterized in that: The structure of the yellow light lamp for anti-ultraviolet and blue-light-free chip process is, from top to bottom, the quantum dot light conversion film, thermal insulation film, OCA adhesive layer, transparent silicone layer, and miniLED blue light chip light source as described in claim 5.

8. The yellow light lamp for anti-ultraviolet and blue-light-free chip manufacturing process as claimed in claim 7, characterized in that: The transparent silica gel layer contains nanoparticles; the nanoparticles are TiO2 or ZrO2; The mass of the nanoparticles is 0.5-5% of the mass of the transparent silica gel layer.

9. The yellow light lamp for anti-ultraviolet and blue-light-free chip manufacturing process as claimed in claim 7 or 8, characterized in that: The OCA adhesive layer contains nanoparticles; the nanoparticles are TiO2 or ZrO2; The mass of the nanoparticles is 1-40% of the mass of the OCA adhesive layer.